2018
DOI: 10.1111/phen.12235
|View full text |Cite
|
Sign up to set email alerts
|

Superior basal and plastic thermal responses to environmental heterogeneity in invasive exotic stemborer Chilo partellus Swinhoe over indigenous Busseola fusca (Fuller) and Sesamia calamistis Hampson

Abstract: Lepidopteran stemborers are the most destructive insect pests of cereal crops in sub-Saharan Africa. In nature, these insects are often exposed to multiple environmental stressors, resulting in potent impact on their thermal tolerance. Such environmental stressors may influence their activity, survival, abundance and biogeography. In the present study, we investigate the effects of acclimation to temperature, starvation and desiccation on thermal tolerance, measured as critical thermal limits [critical thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 94 publications
12
38
1
Order By: Relevance
“…Improvement in cold hardiness following dehydration pre‐treatment may also indicate cross‐tolerance, 83 an indication of shared co‐evolved physiological resistance mechanisms between dehydration and cold stress. This result is in keeping with Mutamiswa et al 84 . who reported improved cold tolerance for Chilo partellus , Busseola fusca and Sesamia calamistis larvae following dehydration pre‐treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Improvement in cold hardiness following dehydration pre‐treatment may also indicate cross‐tolerance, 83 an indication of shared co‐evolved physiological resistance mechanisms between dehydration and cold stress. This result is in keeping with Mutamiswa et al 84 . who reported improved cold tolerance for Chilo partellus , Busseola fusca and Sesamia calamistis larvae following dehydration pre‐treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Tuta absoluta hardening experiments were performed using established experimental protocols for Diptera and Lepidoptera (e.g., Mutamiswa et al, 2018b). To assess the effects of RCH and RHH on T. absoluta physiological traits, hardening temperatures for the two developmental treatment stages (larvae and adults) were established through preliminary assays.…”
Section: Low Temperature Plasticitymentioning
confidence: 99%
“…To assess the effects of RCH and RHH on T. absoluta physiological traits, hardening temperatures for the two developmental treatment stages (larvae and adults) were established through preliminary assays. Cold hardening temperature for larvae was derived from critical thermal minima (CTmin) (Hoffmann et al, 2003;Lee and Denlinger, 2010) and was defined as 6˚C below CTmin (Mutamiswa et al, 2018b) (Table 1). For adults, low hardening temperature was defined as 10˚C above the lower discriminating temperature, consistent with other studies (see (Table 1).…”
Section: Low Temperature Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is in keeping with Pieterse et al (2017) who reported a lack of plasticity in larval B. dorsalis. While phenotypic plasticity is nearly universal in insects (Whitman & Ananthakrishnan, 2009), and that it may facilitate invasiveness (Mutamiswa, Chidawanyika, & Nyamukondiwa, 2018b) and adaptation to changing environments (Chown & Nicolson, 2004), it may appear that it has little or no effect on the invasion edge of B. dorsalis (also see discussions in Pieterse et al, 2017).…”
Section: Discussionmentioning
confidence: 99%